The Interrelation between Stock Prices and the Exchange Rate in Kazakhstan - G. Zh. Azretbergenova (Экономика: стратегия и практика)
A strong economical link has arisen between stock markets and exchange rates as a consequence of increased capital flows between international financial markets. This correlation between stock returns and exchange rates is particularly intriguing for developing countries such as Kazakhstan, whose economies are quite sensitive to capital flows. In the evolving global financial system, comprehension of the correlation between exchange rates and stock prices is vital for policymakers and investors. Knowing this relationship enables the manager to manage risk effectively, contrariwise, it is applied by investors to predict future trends. However, economic and financial policymakers and regulators need to know the interrelation between conversion rate and asset prices, such as stock markets, in order to articulate respective policies. Nevertheless, there are plenty of empirical studies on the interrelation between exchange rates and the stock market in developed and developing countries. This correlation has not been explored in Kazakhstan.   The purpose of this study is to explore the correlation between stock prices and exchange rates in Kazakhstan. The relationship between the variables was analyzed via Johansen Cointegration Test and the VECM model. Upon the results of the analysis, the presence of a long-term correlation between the variables is proved. According to the results of the causality test, the Granger exchange rate is the reason for stock prices in Kazakhstan. There is no causality from stock prices to exchange rates. The results of the study also have a guiding quality in guiding investment decisions for both equity market and foreign money exchange market investors.The null hypothesis that there is nocointegration connection between the variablesis rejected, according to the Trace and MaximumEigenvalue test data in Table 4. In other words,it has been established that the variables have along-term connection. Granger causality test basedon VAR model cannot be used when there is acointegration connection. The VECM (6) modelwill be estimated first, followed by the causalitytest. The results of the causality test predicted usingthe error correction model are presented in Table 5.The exchange rate is the Granger cause of stockprices in Kazakhstan, according to the findings ofthe causality test. There is no relationship betweenstock prices and currency rates.